EXPLORING EFL LEARNERS’ LITERARY COMPETENCE THROUGH THEIR CRITICAL STANCE IN READING NARRATIVE - Wigati D Prasasti; Joesasono O Soelistjowati; Lambang E Suyadjid (Undiksha Press, 2022)
Critical reading has been promoted as the objective of the reading activity in English language learning. However, previous studies have reported that reading comprehension still centres on comprehending the literal meaning and puts aside critical reading as part of their language learning activity. One of the ways to examine EFL learners’ critical reading is to enquire into their literary competence. This study, aiming at exploring the EFL university students’ literary competence from the perspective of critical reading, was conducted in one of the Indonesian private universities. The participants were required to write an essay containing their critical responses towards a literary text. Content analysis on the essay of each participant was done to explore their literary competence. The findings reveal that the participants were able to demonstrate their literary competence that felt into three categories, namely: relating the literary text to one’s experience, empathising with the literary text, and situating the literary text in a wider sociocultural scope. The critical stances reflected in each of the literary competence were respectively accomplished through constructing and engaging; dialoguing and engaging; and reflecting and evaluating. EFL learners’ literary competence is reflected on the critical responses they produced, in which they relate the content of the text with wider out-text contexts. In order to promote critical reading ability, EFL teachers can include aesthetic reading and involve literary competence in the reading activity.